The House of The Kedatukan, Evidence of The Batang Kuis Guardians of The Serumpun Region: Reviving Local History As a Voice Of Almost Forgotten Traditions - M. Sholeh Sihombing; Nia Khairunnisa; Cantika Mawarni; Nehemia Diah Kristalia Sianturi; Delvina Amelia Ramadhani; Ita Khairani (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This study aims to describe the local history of Rumah Kedatukan in Batang Kuis, Deli Serdang, as part of efforts to preserve oral traditions in North Sumatra. Rumah Kedatukan plays an important role in oral historical narratives connected to the adat system of the Serdang Sultanate. This research employs a qualitative approach with an ethnographic design. Data were collected through interviews, observations, and documentation from informants who retain the collective memory of the Rumah Kedatukan story. The analysis applies Ruth Finnegan’s oral literature theory, focusing on composition, transmission, and function. The results show that the Rumah Kedatukan narrative has a distinctive structure, transmitted from generation to generation, and serves as a medium for preserving cultural identity and educating values of leadership and local wisdom. The story also reflects the symbolic meaning of Batang Kuis as the Guardian of Negeri Serumpun, due to its strategic and ceremonial role in the Sultanate of Serdang. Rumah Kedatukan stands as a vital cultural landmark, illustrating the interplay of tradition, spirituality, and sociopolitical systems in Malay Serdang culture. These findings affirm the urgency of documenting oral traditions to safeguard endangered local histories.